2021
DOI: 10.1002/admi.202101344
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Structural Flexibility in Plasmon‐Driven Coupling Reactions: Kinetic Limitations in the Dimerization of Nitro‐Benzenes

Abstract: molecules simultaneously, which facilitates coupling reactions of two or more molecules. [7][8][9] On the other hand, nanoscale heating can increase the speed of molecular reorganization and surface diffusion, thereby increasing the rate of favorable reactive encounters. Several important examples of plasmon-driven bond formation were demonstrated in recent years, [10,11] including CC bond formation in hydrocarbons, [7,12] Suzuki-Miyaura type reactions, [13] and molecular dimerization reactions by NN bond fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…(iii) In addition, also an electron transfer from the metal to the molecule affects the work function, which has been described elsewhere in more detail for the present system. 37 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(iii) In addition, also an electron transfer from the metal to the molecule affects the work function, which has been described elsewhere in more detail for the present system. 37 …”
Section: Resultsmentioning
confidence: 99%
“…(iii) In addition, also an electron transfer from the metal to the molecule affects the work function, which has been described elsewhere in more detail for the present system. 37 (iv) A fourth effect is a possible shi of the Au 4f signals due to the different chemical environment of the gold sulfur bond. The shi for NTP coupled to a single Au atom compared to pure Au has been calculated by DFT to be 1.3 eV to higher BE, which is in good agreement with previously reported values for Au-S 65 and other hybridized Au species.…”
Section: Depth Dependent Measurements Of Isolated Aunpsmentioning
confidence: 99%
See 1 more Smart Citation
“…1440 cm -1 are not related to the original MBD molecules but rather to an azobenzene derivative (Figure 5a), similar to the very common dimercaptoazobenzene (DMAB). 11,26 Also, the peak for the N2 + stretching around 2200 cm -1 is not observed. Since the diazonium moiety is very reactive, it is possible that the self-assembled MBD molecules are sufficiently close to each other on the gold surface to react with each other and dimerize.…”
Section: Plasmon-induced Crosslinking Reactionmentioning
confidence: 91%
“…First, the Raman spectra showed that the diazonium molecules are selfassembled in a dimer form, resembling the typical DMAB structures. 26 Second, upon continuous excitation of the surface plasmon, the Raman peak assigned to the N=N vibrational modes decreases in intensity, while the C=C peak is broadened with time, suggesting the crosslinking of the adsorbed molecules accompanied by removal of the nitrogen.…”
Section: Introductionmentioning
confidence: 98%